Improving the Competitiveness of Culinary Businesses through Education on Halal Certified Food and Beverage Products in Masaingi Village - Parani, Syamsul Bahri Dg.; Muslimin, Muslimin; Miru, Sulaeman; Nofal, Mohammad; Dwiwijaya, Kadek Agus (Sarana Ilmu Indonesia (salnesia), 2025)
In the era of globalization, halal certification has become a crucial element in the marketing of food, beverages, and pharmaceuticals, particularly for culinary businesses. This is due to the increasing demand from Muslim consumers who require products that comply with halal standards. In Islam, consumed food and products must be halal and thoyyib, as prescribed in the Qur'an and Hadith. However, most SMEs businesses in Desa Masaingi have yet to obtain halal certification, which ensures that their products and services meet the halal standards set by the Halal Product Assurance Agency (BPJPH). This community service aimed to enhance the knowledge and awareness of both the community and business actors about the importance of halal certification, halal production processes, and the market opportunities that can open up by obtaining such certification. The methods used included location observation, inspection of home industries, education on halal and thoyyib products, and registration for Business Identification Numbers (NIB) and halal certification through the OSS application and BPJPH official website. The results of this community service showed that these activities successfully improved the community's understandingof halal principles and motivated culinary business actors to obtain halal certification. Consequently, culinary business actors in Desa Masaingi, particularly in the Pangi tourist area, are expected to be more open to the halal certification process and enhance their product competitiveness in broader markets.